Corporate governance and corporate failures : an empirical evidence of Malaysian public listed companies - Marziana bt Madah Marzuki (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2005)
In the wake of the collapse of several major corporations such as Enron, many corporations are urged to recognize the factors behind such corporate failures. Corporate failure involves the cessation of trading or activity of a business, which is generally preceded by financial distress. It is believed that a lack of corporate governance is one of the factors and thus, one of the efforts to prevent major corporate failures is by increasing focus on corporate governance reforms. This research studies the association between corporate governance attributes and financial distress position which is proxied by PN4 status of Malaysian Public Listed companies. In general, the aim of this study is to answer the question whether corporate governance attributes provides insight about the potential for corporate failures in Malaysia. Another objective for this study is to assess to what extent the financial indicatcrs such as profitability, liquidity and leverage affect the possibility of corporate failure. A comparison between PN4 firms and healthy firms are made in order to know the characteristics of PN4 Companies in Malaysia. The research is concerned with three corporate governance attributes which are board composition, leadership structure and ownership structure by the board of directors and three financial indicators which are liquidity, profitability and leverage. PN4 companies are chosen as proxy for corporate failure in Malaysia as they fail to comply with the obligations set out under KLSE requirement Practice Note 4 and thus, they have to restructure back its organization in order to be re-listed as original sector on KLSE board. For the purpose of this study all Malaysian Public Listed Companies which are listed under PN4 condition in the main board as at 31 December 2002 are included as a sample. This period is chosen as it is the latest financial year-end period of PN4 companies. It uses mean descriptive statistics, the paired sample t-test and binary logistic regression for statistical analysis. Based on the results, most of the hypotheses are not supported. The results showed that there is insignificant difference between PN4 companies and healthy firms in term of board composition, leadership structure and ownership structure. Instead, it is found that PN4 companies do have higher proportion of outside directors than healthy firms. Thus, it can be concluded that there is no association between corporate governance attributes and corporate failures in Malaysia. However, the results found that there is significant difference for financial indicators such as profitability and liquidity. Hence, PN4 companies can be described as firms that have lower profitability and liquidity as compared to healthy firms.